Impedance decoupling strategy to enhance the real-time powering performance of TENG for multi-mode sensing - Hao Sun; Yuxuan Xia; Jinyan Zhi; Jun Ma; Jinwan Chen; Zhekai Chu; Weihao Gao; Shuhai Liu; Yong Qin (Nature Communications)
Abstract Triboelectric nanogenerator can scavenge mechanical energy from environment to power sensor networks, becoming increasingly important in fields like healthcare and infrastructure. However, due to its impedance coupling with sensor networks, stimuli-induced impedance changes of sensor networks will result in an inconstant output of triboelectric nanogenerator, leading to a poor real-time powering performance for sensor networks as compared with a constant voltage source; designing triboelectric nanogenerator with high powering performance to real-timely power sensor networks faces great challenges. Herein, an impedance decoupling strategy is proposed to enhance the real-time powering performance of triboelectric nanogenerator by decoupling impedances of triboelectric nanogenerator and sensor network. A shunt circuit composed of a small fixed resistor is introduced to stabilize the whole impedance of the shunt circuit and the sensor network, making the output voltage of triboelectric nanogenerator on sensors almost unchanged, and thus cut off the impedance coupling. Our results show that the strategy highly enhances the real-time powering performance of triboelectric nanogenerator for sensor networks, and achieves multi-mode sensing with relative errors as low as –4.6%, comparable to that powered by a commercial power source. This work provides useful guidance for designing triboelectric nanogenerator for multi-mode sensing, and contributes to its practical applications.